BENIGN PHYLLODES TUMOR ARISING IN AXILLARY BREAST TISSUE; A RARE CASE WITH AVAILABLE REVIEW OF LITERATURE - DASH, MONICA; MISHRA, PRAGNYA PARAMITA; PANDA, PREMANAND (International Journal of Current Pharmaceutical Research, 2025)
Anatomical variation known as accessory breast tissue arises during embryogenic development. The axilla is where it most commonly occurs. Accessory breast tissue may experience both benign and malignant processes similar to those in normal breast tissue. We describe a 40-year-old woman who had a palpable mass at her left axilla and who later developed a benign phyllodes tumor in her axillary breast tissue. Microscopy revealed an encapsulated tumor composed of cells arranged in singles, compressing the epithelial cells into a leaf-like (phyllodes) pattern with a mild lymphocytic stromal response. Although phyllodes tumors in axillary breast tissue are a very uncommon occurrence, this case study provided additional information on the tumor, which might promote improvements in disease management.